Association of A1AT With Poor Functional Outcome in Patients With Acute Ischemic Stroke - Paula García‐Rodríguez; Marcel Lamana‐Vallverdú; Daisy R. Guamán‐Pilco; Anna Penalba; Laura Ramiro; Alba Simats; Júlia Faura; Alejandro Bustamante; Noelia Díaz‐Troyano; Joan Montaner (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aimed to investigate whether A1AT (α‐1 antitrypsin) bloodstream levels, measured acutely after ischemic stroke, can predict the outcome of patients with stroke. Methods and Results Two cohorts of patients with stroke were studied independently and retrospectively: a pilot cohort of 59 patients and a larger replicative study with 527 patients. Blood samples were drawn at hospital admission (<6 hours after stroke onset) before any treatment was given. A1AT levels were analyzed. Patients were followed after the event, and functional outcomes were evaluated at in‐hospital (discharge) and midterm (third month) follow‐up according to the modified Rankin Scale (considering modified Rankin Scale score >2 a poor outcome). Association studies between A1AT levels and functional outcomes were conducted. We also evaluated the added value of A1AT as a prognostic biomarker over the clinical model (sex, age, premorbid modified Rankin Scale and National Institutes of Health Stroke Scale scores) with the likelihood ratio test. In both studies, the levels of A1AT were higher in patients who had worse outcomes, were older, and had higher National Institutes of Health Stroke Scale scores at admission. In the pilot study, higher levels of A1AT were also associated with death at discharge and at 3 months after stroke (P=0.035 and P=0.023, respectively). The addition of A1AT to the clinical model did not show enough evidence of increasing the fit of the model to the data in either cohort. Conclusions Based on our data, we cannot claim that A1AT is an independent biomarker of ischemic stroke. Nevertheless, A1AT is potentially involved in stroke outcomes and might be explored as a potential therapeutic target.